The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1002/jso.2930140309
|View full text |Cite
|
Sign up to set email alerts
|

Liposarcomas: Prognosis and management

Abstract: Fifty-one evaluable patients with liposarcomas were reviewed. Two-thirds of the patients were referred after local recurrence. One-third with primary surgery at RPMI had local recurrence rate of 31.6%. Overall, one or more local recurrences presented in 78% of patients. Pulmonary metastases, occurred in 45%, while liver metastases in 13.6%. Most common primary sites were the lower extremity, followed by the retroperitoneal area and upper extremity. Median survival is better for upper and lower extremities than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
4

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 10 publications
0
36
0
4
Order By: Relevance
“…Intermuscular lipomas should also be distinguished from liposarcomas in terms of malignancy. The possibility of liposarcoma should be considered when a fatty tumor with a dimension of >10 cm has shown rapid growth (11). Imaging examinations may be of crucial importance in the differentiation between the two tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermuscular lipomas should also be distinguished from liposarcomas in terms of malignancy. The possibility of liposarcoma should be considered when a fatty tumor with a dimension of >10 cm has shown rapid growth (11). Imaging examinations may be of crucial importance in the differentiation between the two tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Intramuscular lipomas, however, arise between muscle fibers, pass through the intermuscular septa and infiltrate the surrounding tissues, rendering removal of the lesion from the nearby muscles difficult (8)(9)(10). Liposarcomas are malignant soft tissue tumors reported in radiological as well as histological findings to comprise 7-27% of the soft tissue sarcomas (11), and be able to mimic inter-and intramuscular lipomas, rendering the diagnosis and choice of treatment difficult (12).…”
Section: Introductionmentioning
confidence: 99%
“…Well-differentiated liposarcomas, as seen in patient 5, account for approximately 40% to 45% of liposarcomas (1). Recent rapid growth, size larger than 5 cm and intramuscular location have all been reported to be risk factors for malignancy (1,5,6).…”
Section: Discussionmentioning
confidence: 98%
“…There are also reports that the intramuscular location of a lipoma is a risk factor for malignancy [2,3]. The lower extremities are one of the most common sites for liposarcomas [8,9]. In this site, when diagnosis of liposarcoma is sure, Campbell et al recommends wide excision or amputation if needed [10].…”
Section: Discussionmentioning
confidence: 99%
“…They have reported a high probability of recurrence (91%) secondary to conservative initial treatment. Some authors have reported that postoperative adjuvant radioterapy lengthens the median survival rate when surgical excision has not been adequate [7,8,10].…”
Section: Discussionmentioning
confidence: 99%